2021
DOI: 10.3390/jdb9020012
|View full text |Cite
|
Sign up to set email alerts
|

Mutation in the Ciliary Protein C2CD3 Reveals Organ-Specific Mechanisms of Hedgehog Signal Transduction in Avian Embryos

Abstract: Primary cilia are ubiquitous microtubule-based organelles that serve as signaling hubs for numerous developmental pathways, most notably the Hedgehog (Hh) pathway. Defects in the structure or function of primary cilia result in a class of diseases called ciliopathies. It is well known that primary cilia participate in transducing a Hh signal, and as such ciliopathies frequently present with phenotypes indicative of aberrant Hh function. Interestingly, the exact mechanisms of cilia-dependent Hh signaling transd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 115 publications
1
2
0
Order By: Relevance
“…Perhaps this is not surprising since the spatiotemporal development of GI smooth muscle has been shown to have regional-specific differences ( Bourret et al, 2017 ; Graham et al, 2017 ). Our results are in accordance with recent findings in the related chicken mutant talpid2 ( Brooks et al, 2021 ).…”
Section: Discussionsupporting
confidence: 94%
“…Perhaps this is not surprising since the spatiotemporal development of GI smooth muscle has been shown to have regional-specific differences ( Bourret et al, 2017 ; Graham et al, 2017 ). Our results are in accordance with recent findings in the related chicken mutant talpid2 ( Brooks et al, 2021 ).…”
Section: Discussionsupporting
confidence: 94%
“…Previous reports from our lab and others have documented the craniofacial and skeletal phenotypes present in ta 2 embryos (Abbott et al, 1960(Abbott et al, , 1959Bonatto Paese et al, 2022, 2021b, 2021aBrooks et al, 2021;Brugmann et al, 2010;Caruccio et al, 1999;Chang et al, 2014;Dvorak and Fallon, 1991;Harris et al, 2006;Schneider et al, 1999;Schock et al, 2015). To better understand the molecular etiology of these phenotypes, we performed a temporal analysis of mandibular development, initially focused on Meckel's cartilage.…”
Section: Results Ta 2 Embryos Presented With Ectopic Bilateral Cartil...mentioning
confidence: 99%
“…Previous studies demonstrated that the combinatorial action of FGF8 and SHH is required to drive cartilaginous outgrowth in the developing craniofacial complex (Abzhanov and Tabin, 2004; Hu et al, 2003) while other studies indicated that exogenous BMP4 expression can lead to ectopic craniofacial chondrogenesis (Barlow and Francis-West, 1997; Hu et al, 2008; Nonaka et al, 1999; Semba et al, 2000). With the knowledge that primary cilia regulate signal transduction and the ta 2 embryo has dysregulated Hedgehog signaling in the developing craniofacial complex (Brooks et al, 2021; Brugmann et al, 2010; Chang et al, 2014), we sought to examine the relative expression patterns of BMP4 , FGF8 and SHH in control and ta 2 MNPs.…”
Section: Resultsmentioning
confidence: 99%
“…C2CD3 localises to the distal appendages that anchor the BB to the cell membrane [53,54]. It is required for ciliogenesis, for recruiting proteins to the BB, for removing protein from the BB, for the docking of vesicles to the BB, for distal appendage assembly, for controlling centriole elongation, and for regulating HH signalling in a tissue-specific manner [54][55][56][57]. In addition to the BB protein C2CD3, some proteins that localise to the TZ are associated with cell death.…”
Section: Ciliary Base Proteins and Cell Deathmentioning
confidence: 99%